Comparison of Outcomes Between Subtotal Fenestrating Cholecystectomy and Open Conversion Cholecystectomy in Cases of Frozen Calot’s Triangle; A Single Centre Experience - Bukhari, Sarah Tauseef; Wattoo, Nasir Mehmood; Khan, Waseem Ahmed; Badar , Mubashra; Javed, Romassa; Zahid, Sana (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the outcomes of laparoscopic subtotal fenestrating cholecystectomy (LSFC) and open conversion cholecystectomy (OCC) performed for difficult gallbladder surgery with frozen calot’s triangle (FCT).Study Design: Prospective comparative study.Place and Duration of Study: Department of General Surgery, Pak-Emirates Military Hospital Rawalpindi, Pakistan from Jan 2023 to Jan 2024.Methodology: The study population included adult patients who underwent laparoscopic cholecystectomy for gallbladder pathology. The study included a total of eighty-six (n=86) patients. 43 patients underwent LSFC and 43 patients underwent OCC because of FCT. Both groups were compared in terms of Operation time, intra-operative complications, postoperative outcomes, and length of stay (LOS) in the hospital.Results: The mean age of eighty-six (n=86) patients was 47.70±0.67 years, including 60(69.8%) males and 26(30.2%) females. Patients who underwent LSFC had operation time 91.90±10.32 minutes, length of stay in hospital 4.86±0.70 days, and biliary fistula was formed in 8(18.60%) patients. Patients who underwent OCC had operation time 112.34±12.45 minutes, length of stay in hospital 7.67±0.96 days, bile duct injury in 2(4.65%) patients and formation of biliary fistula in 1(2.32%) patients.Conclusion: LSFC is associated with reduced operation time, decrease LOS in hospital and lesser incidence of bile duct injury as compared to OCC. However, the incidence of formation of biliary fistula was more with LSFC.